2017
DOI: 10.18632/oncotarget.18995
|View full text |Cite
|
Sign up to set email alerts
|

Hyperosmotic stress stimulates autophagy via polycystin-2

Abstract: Various intracellular mechanisms are activated in response to stress, leading to adaptation or death. Autophagy, an intracellular process that promotes lysosomal degradation of proteins, is an adaptive response to several types of stress. Osmotic stress occurs under both physiological and pathological conditions, provoking mechanical stress and activating various osmoadaptive mechanisms. Polycystin-2 (PC2), a membrane protein of the polycystin family, is a mechanical sensor capable of activating the cell signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
44
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 81 publications
(104 reference statements)
5
44
1
Order By: Relevance
“…The NFE2L2 pathway may have been activated in response to autophagy that may have been caused by increased osmolarity in culture medium. It was previously reported that various concentrations of sorbitol and mannitol caused hyperosmotic stress and autophagy in human colon cancer cell line HCT116 (26). That mechanism may have promoted expression of NFE2L2 gene in Caco-2 cells in our case.…”
Section: Discussionsupporting
confidence: 52%
“…The NFE2L2 pathway may have been activated in response to autophagy that may have been caused by increased osmolarity in culture medium. It was previously reported that various concentrations of sorbitol and mannitol caused hyperosmotic stress and autophagy in human colon cancer cell line HCT116 (26). That mechanism may have promoted expression of NFE2L2 gene in Caco-2 cells in our case.…”
Section: Discussionsupporting
confidence: 52%
“…The 'growth/survival & inflammation' group contain proteins that counteract apoptotic responses or indicate growth, proliferation, and inflammatory stimulation. The group contains phosphorylated forms of Bad 45 , Bcl2 46 , two proapoptotic proteins, mTOR 47 , a key node in the cell growth pathway, ribosomal protein S6 48 , a marker for active translation, and p-ZAP70 49,50 , a marker for activated inflammatory signaling.…”
Section: Resultsmentioning
confidence: 99%
“…Recent reports highlighted that downstream of AMPK activation and mTOR inhibition, hyperosmotic stress triggers autophagy [11, 13, 17]. Thus, autophagic markers were evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…Autophagy and microtubule remodeling have been proposed to play a prominent role in the osmoprotective cell response [12]. In this regard, mechanical sensors are important elements in activating the cell signaling pathways required for cell adaptation and survival [13]. Nevertheless, uncontrolled hyperosmotic stress can lead to apoptotic cell death [10].…”
Section: Introductionmentioning
confidence: 99%